A review on recent advances in hybrid supercapacitors: Design, fabrication and applications. (March 2019) - Muzaffar, Aqib; Ahamed, M. Basheer; Deshmukh, Kalim; Thirumalai, Jagannathan
Abstract: Hybrid supercapacitors with their improved performance in energy density without altering their power density have been in trend since recent years. The hybrid supercapacitor delivers higher specific capacitance in comparison to the existing electric double layer capacitor (EDLC) and pseudocapacitors. Generally, the asymmetric behavior of hybrid supercapacitors which is the combination of EDLC and pseudocapacitor acts as an enhancer in its respective capacitance values. This asymmetric approach marks a new beginning towards the much-needed pollution free, long lasting and proficient energy-storing performance. Corresponding to their utilization in hybrid electric vehicles and similar sort of power necessity based devices; the research in developing new advanced storage devices finds an enormous and vast future ahead. The most significant factor for the energy efficient applications demands a considerably higher ratio of surface to the volume by incorporation of new materials. This review article gives an overview of recent advances in the development of hybrid supercapacitors, storage mechanism, criteria of formation, components, different electrode and electrolyte materials, electrochemical profile assessment, design fabrication and their applications. Highlights: The current status and the advancement of supercapacitors are discussed in this review. The principles, classification and the mechanism of energy storage are discussed. Finally, various applications of supercapacitors have been discussed.